Imagery interventions in health behavior: A meta-analysis - Conroy, D.; Hagger, Martin (American Psychological Association, 2018)
© 2018 American Psychological Association. Objective: Imagery-based interventions represent an inexpensive, potentially effective technique for changing health behavior and promoting adaptive health outcomes. However, research adopting mental imagery techniques in health behavior interventions has shown considerable variability in effects across studies. In the present analysis we present a quantitative synthesis of the effectiveness of mental imagery interventions in health behavior and tested effects of key moderators. Method: A systematic database search for studies adopting imagery interventions in health behavior and related outcomes was conducted with additional manual searches and direct author contact for unpublished studies. Data were extracted for imagery intervention effects on behavioral, psychological, and physiological outcomes, and for candidate moderators. Results: Twenty-six studies of mental imagery intervention effects comprising 33 independent data sets met eligibility criteria for inclusion in the review. Mental imagery interventions led to nontrivial, small averaged corrected effect sizes on postintervention behavior, intention, perceived control, and attitude, and a small-to-medium sized effect on postintervention physiological measures. Substantive heterogeneity in the effects meant that a search for moderators was warranted. Moderator analyses indicated larger effects of imagery interventions on health behaviors in studies on older, nonstudent samples, when detailed instructions were provided, in studies with higher methodological quality scores, and in studies of longer duration. Effect sizes for imagery on behavioral and physiological outcomes were larger than effects on psychological outcomes. Conclusion: Results support effects of mental imagery interventions on health behaviors, identify conditions in which they may be more effective, and point to how future imagery interventions might be optimized.